Analisis Pelaksanaan Pidana Ganti Kerugian (Denda) dalam Tindak Pidana Korupsi - Bambang Hartono (Universitas Bandar Lampung (UBL), 2011)
The corruption criminal based on Corruption law No.31 year 1999 jo CorruptionLaw No.20 year 2001 Change of Corruption law No.31 year 1999, then proved howbig executant deed consequence country loss and furthermore judge determine finemagnitude total that based on paragraph in law that base decision, when does Changeloss criminal not so be can be replaced cage. Change loss criminal can evoke scaredeffect for corruption doing an injustice executant, because besides to change loss,also must endure prison criminal and return state’s finance loss, when does changeloss criminal not paid and they also must endure cage criminal. But in fact, changesloss criminal doesn’t give scared effect for corruption doing an injustice executant,this matter is proven by stills corruption doing, an injustice quantity that in Indonesia.